2016
DOI: 10.1016/s1474-4422(16)30057-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of interface astroglial scarring in the human brain after blast exposure: a post-mortem case series

Abstract: Defense Health Program of the United States Department of Defense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
154
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(166 citation statements)
references
References 36 publications
10
154
2
Order By: Relevance
“…In addition, many soldiers who suffer mild TBIs later develop posttraumatic stress disorders and progressive dementia. Some studies argue that these signature injuries of the recent conflicts in Afghanistan and Iraq are the result of exposure to blast waves from improvised explosive devices (34,(64)(65)(66)(67). Similar to AD, biochemical analyses of NFTs isolated from CTE patients have shown that these aggregates consist of both 3R and 4R tau isoforms (24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many soldiers who suffer mild TBIs later develop posttraumatic stress disorders and progressive dementia. Some studies argue that these signature injuries of the recent conflicts in Afghanistan and Iraq are the result of exposure to blast waves from improvised explosive devices (34,(64)(65)(66)(67). Similar to AD, biochemical analyses of NFTs isolated from CTE patients have shown that these aggregates consist of both 3R and 4R tau isoforms (24).…”
Section: Discussionmentioning
confidence: 99%
“…Since larger aggregates of p-tau would not be as free to move readily through the brain ECS by diffusion as unbound monomers, such aggregates likely become trapped within the tissue, particularly the tissue space bordering venules and large veins; this sequence of events would be expected to further impede the subsequent clearance of p-tau and other waste constituents over time. Interestingly, military personnel exposed to blast shockwaves (e.g., from explosive devices) also show a characteristic pattern of GFAP and p-tau immunoreactivity with prominent astroglial scarring at brain-fluid interfaces including the subpial region and perivascular spaces [156].…”
Section: Cns Pathologies and Disturbances Of Brain Fluidsmentioning
confidence: 99%
“…These findings are in concordance with postmortem studies of boxers and military personnel who had repetitive trauma to the head, showing increased astroglial activation. 3,23 Experimental and postmortem case-control studies suggest that athletes who have been exposed to repetitive head trauma are at increased risk of developing brain pathology, such as Ab deposition and tau pathology. 3,4,12,13 In the context of AD, numerous studies have shown that reduced CSF Ab42 concentrations correlate strongly with positive amyloid PET finding, 24 and a recent study also suggests that the reduction in CSF Ab42 is an earlier indicator of cerebral Ab deposition than amyloid PET.…”
mentioning
confidence: 99%